Bi-univocal relationship between the game model and training model in handball - Cazan, F.; Georgescu, A. (Science, Movement & Health, 2018)
This thesis demonstrates that there is a bi-univocal relationship between the play model`s dimensions (expressed by value parameters) and the training model (objectives - contents - strategies - evaluation), relationship that must be capitalized in the benefit of the continuous growth of the players and team`s performance capacity. Purpose: Bi-univocal relationship between the model and model training game is a concept supported by many specialists, (L.Teodorescu, 1975, Colibaba, D. 2007, Bota I. 1988, Bompa T. 2001) more of theoretical and less practical standpoint. This paper proposes a very practical way of implementing this relationship. In other words, try to answer the questions: how to convert design dimensions of play in the instructional objectives of the training process and how in turn the preparation leads to the continued improvement of the capacity of team performance? Methods: To confirm this hypothesis, we took the example of a Romanian handball team HCM Constanta. Thus the competitive year 2008/2009 we studied performance behavior in the championship game. Using all means at their disposal recording (protocols, DVDs matches records, official documents etc.) we managed to outline some general aspects and especially the main dimensions of the game provided by the team. Conclusions: The dimensions of game design can be converted to instructional objectives, and these in turn triggers the entire axis generative methodological approach (objectives - content - strategies - evaluation) toward continued growth in capacity performance.